From Living Law to National Law: Theoretical Reconstruction of Applying Islamic Law in Indonesia - Siti Rohmah; Azka Rasyad Alfatdi (Peradaban Journal of Law and Society, 2022)
Islam entered and developed in Indonesia by bringing new values to life. The entry of Islam amid the plurality of Indonesian society then gave rise to a distinctive pattern of interaction. The intersection of Islamic values with Indonesian cultural values gives rise to various patterns of interaction. Now Islamic values have been accepted as a living value in Indonesian society. Acceptance of Islamic values and norms also occurs within the jurisdiction. Islamic law developed together with the customary law system and western law. Even now, Islamic law has become one of the important sources of law in developing national law. The inclusion of Islamic law in The national legal system certainly goes through long social and political dynamics and involves various parties. This article aims to examine the process of accepting Islamic law in the national legal system from a theoretical perspective. The study was conducted with a library research approach. This study is needed as material for reflection and projection of the development of Islamic law in Indonesia in the future.